Experiences inside the Ubiquitous Oulu Smart City. - Gil-Castineira, Felipe; Costa-Montenegro, Enrique; Gonzalez-Castano, Francisco J.; Lopez-Bravo, Cristina; Ojala, Timo; Bose, Raja (Computer (00189162), 2011)
The UrBan Interactions (UBI) research program, coordinated by the University of Oulu, has created a middleware layer on top of the panOULU wireless network and opened it up to ubiquitous-computing researchers, offering opportunities to enhance and facilitate communication between citizens and the government.